Policy and Culture: From Machiavelli’s Political Philosophy to Kipling’s Political Prophecies - K. M. Dolgov; E. I. Starikova (Vestnik MGIMO-Universiteta)
The article is concerned with interrelationship of policy and culture, in particular N.Machiavelli's political philosophy and its reflection in some short stories by R.Kipling, one of the most recognized representatives of the British imperial thought. Policy and culture have traditionally been considered almost incompatible spheres of human activity as policy tended to become more and more severe, cynical, "dirty", while culture aspired to develop supreme values and perfect ideals. Sometimes the direct confrontation between policy and religion, policy and morals, policy and law, policy and literature, policy and art in the broad sense of the word could occur. The greatest Renaissance masters - Michelangelo, Leonardo da Vinci, Rafael etc. - actively opposed any evil manifestations: evil ideas, evil words, evil doings, expressing in their masterpieces the highest ideals and values. However, these ideals and values drastically diverged from the reality, political and public relations of the time, the "dirty" policy conducted by the rulers of numerous Italian principalities. It is no coincidence that N.Machiavelli develops his new political philosophy aiming not only to create the strong unitary state, but also to overcome this "dirty" policy at least to a certain extent. Therefore, describing the mechanism of the "dirty" policy that opposes high culture, N.Machiavelli introduces a new political philosophy which should be based on the highest ideals and values. As far as literary art is concerned, one can easily see that such world famous novelists as Kipling, Chekhov, Maupassant and many others reflected in their short stories that very longing for highest values and ideals which are almost absent in political doctrines and political practice. The true policy is necessarily based on the true culture and its values and ideals, whereas the true culture is indispensably connected with the true policy.